Metaphors as expressions of followers' experiences with academic leadership. Issue 5 (2nd September 2016) - Skorobohacz, Christina; Billot, Jennie; Murray, Shannon; Khong, Lana Y. L.
ABSTRACT: Researchers continue to investigate and understand leadership in higher education. However, leadership does not stand alone; it is part of an interactive dyad with followers. Building on a previous study that aimed to unpack academics' experiences of leadership in higher education with a view to enhancing leadership practices, this paper creatively examines metaphors in order to understand how followers interpret academic leadership, followership and follower–leader interactions. Data were gathered from academics in follower roles through written narratives or face-to-face interviews in accordance with participants' preferences. Drawing on a social constructionist perspective and a metaphorical conceptual framework, we align with Lakoff and Johnson [1980. Metaphors we live by . Chicago: University of Chicago Press] who claim that metaphors pervade thought and action. Our findings illuminate followers' understandings of leadership efficacy; their multifaceted responses to particular encounters with leaders and the complexities of following and leading in university workplaces. We demonstrate how metaphors can explain some of the concerns and constraints shaping follower and leader interactions in academia. Our analysis highlights the importance of framing leadership as a relational and dynamic construct.